I Don't Care - Fogliano, Julie; Idle, Molly Schaar; Martinez-Neal, Juana (New York : Holiday House, 2022)
"Two friends share their delight in the little things that set them apart, and the big things that bring them together"--
Keywords: Friendship -- Juvenile fiction; Individual differences -- Juvenile fiction; Friendship -- Fiction; Individual differences -- Fiction; Stories in rhyme; Stories in rhyme; Picture books